2023
DOI: 10.3390/en16010568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Economy on Energy Supply Chain Efficiency: Evidence from Chinese Energy Enterprises

Abstract: The global industrial chain and energy supply chain are being reconfigured at an accelerated pace, and the uncertainty of China’s energy supply security is growing significantly. Empowering energy supply chains through the digital economy (diec) has a positive effect on accelerating the transformation of China’s energy supply structure. This paper discusses the effect and mechanisms of the digital economy on energy supply chain efficiency (esce). Specifically, based on the panel data of 112 energy enterprises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…With the deepening of the integration of digital technologies, automatic early warning monitoring and control at the millisecond level will be expected in the future. For example, intelligent solutions help improve supply chain link efficiency, such as enterprise production and operation, and improve the efficiency of energy resource allocation (Fu et al, 2023). Supply chains for specific energy sectors, such as the energy and gas industry, are complex systems that involve sales decisions by oil suppliers/distributors, market prices, refining operations, gantry operations, and product transportation.…”
Section: Direct Impact Of Digital Technology On Eementioning
confidence: 99%
“…With the deepening of the integration of digital technologies, automatic early warning monitoring and control at the millisecond level will be expected in the future. For example, intelligent solutions help improve supply chain link efficiency, such as enterprise production and operation, and improve the efficiency of energy resource allocation (Fu et al, 2023). Supply chains for specific energy sectors, such as the energy and gas industry, are complex systems that involve sales decisions by oil suppliers/distributors, market prices, refining operations, gantry operations, and product transportation.…”
Section: Direct Impact Of Digital Technology On Eementioning
confidence: 99%
“…The innovation-leading effect will be stimulated, thus help reducing energy consumption and improving the efficiency of industrial green innovation. At the same time, by optimizing the traditional industrial structure, changing the production mode and improving the efficiency of the supply chain (Luo et al, 2023;Fu et al, 2023;Mikhaylova et al, 2021), the digital economy forces the industrial upgrading of enterprises. These can help enterprises gain new competitive advantages to better exchange and integrate knowledge with external organizations, thus enhancing innovation capabilities.…”
Section: Mediating Role Of External Knowledge Sourcesmentioning
confidence: 99%
“…Zhao et al (2020) found that the digital economy can enhance entrepreneurial activity and promote high-quality economic development using empirical research on the panel data of 222 cities above the prefecture level in China. In addition, several studies have analyzed the impact of DT on trade in services (Zhou L. et al, 2023), total factor energy efficiency (Fu et al, 2023;Huang et al, 2023), knowledge innovation (Orlando et al, 2020;Wang and Li, 2023), economic growth (Qu et al, 2017), air pollution , and green total factor productivity (Guo et al, 2022;Zhao et al, 2022).…”
Section: The Economic Effects Of Digital Technologymentioning
confidence: 99%